Satire in Modern Nigerian Theatre: A Historical Exploration - Adeoti, G. R. (2014)
Satire is a literary mode usually taken as a brand of comedy. But like Proteus, the ever-changing Greek sea-god, it has flexibly assumed various artistic shapes and forms and has found expression outside' the territories of literature, in sculpture, painting, cartoon, cinema and music. Thus, it has earned a separate identity worthy of scholarly attention.